The Extractive Industry’s Decarbonization Potential Using Electrification and Hydrogen Technologies - Antonis Peppas; Chrysa Politi; Maria Taxiarchou (Hydrogen, 2025)
The challenge of achieving net-zero CO2 emissions will require a significant scaling up of the production of several raw materials that are critical for decarbonizing the global economy. In contrast, metal extraction processes utilize carbon as a reducing agent, which is oxidized to CO2, resulting in considerable emissions and having a negative impact on climate change. In order to abate their emissions, extractive industries will have to go through a profound transformation, including switching to alternative climate-neutral energy and feedstock sources. This paper presents the authors’ perspectives for consideration in relation to the H2 potential for direct reduction of oxide and sulfide ores. For each case scenario, the reduction of CO2 emissions is analyzed, and a breakthrough route for H2S decomposition is presented, which is a by-product of the direct reduction of sulfide ores with H2. Electrified indirect-fired metallurgical kiln advantages are also presented, a solution that can substitute fossil fuel-based heating technologies, which is one of the main backbones of industrial processes currently applied to the extractive industries.